Developing a Modified UNO-Based Card Game to Enhance Eighth-Grade Students’ Grammar in Narrative Texts - Ismi Azizah; Istina Atul Makrifah; Tyas Alhim Mubarok; Winda Khoirun Nisak (PROJECT (Professional Journal of English Education), 2026)
This study aims to develop a modified UNO card game as a learning medium to teach eighth-grade students’ grammar in narrative text. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The study was carried out at SMP Islam Baabussalaam, where a lack of interactive technology and a focus on textbook-based education made it difficult for students to learn grammar, especially the simple past tense. The product developed integrates grammar exercises into an interactive UNO card game to promote engagement and contextual learning. The validation results showed that the instrument, media, and material were highly valid, with scores of 93.75% (very valid), 97.05% (very valid), and 98.21% (very valid), respectively. The implementation results indicated positive student response, yielding a feasibility score of 84.31% (very feasible), classified as highly feasible. The findings indicate that the modified UNO card game serves as a feasible, practical, and effective instructional media that improves students' motivation and comprehension of grammar in narrative text.